16+1 Initiative: Cooperation strategy between China and Central and Eastern European countries - mohsen keshvarian azad; Mobarakeh sedaghati (رهیافتهای سیاسی و بین المللی)
China's foreign policy continues its multilateral economic plans in the international arena such as; "Belt and Road Initiative", "Made in China 2025", " Health Silk Road", "Asian Infrastructure Investment Bank" and..., have considered cooperation with European countries. In the last decade, Beijing has established multilateral mechanisms and initiatives at the regional, transregional and bilateral (pivot countries) levels and in the form of these multilateral initiatives, it includes economic, political, and cultural dimensions with different regions, especially Europe. In this framework, the "16+1 Initiative" was defined in 2012 as a complement to the " Belt and Road " by China and Central and Eastern European countries to develop multilateral cooperation. The purpose of this article is to explain the impact of this multilateral initiative on the cooperation between China and the countries of Eastern and Central Europe, and the question of how the multilateral initiative 1+16 is the context of the interwoven cooperation between China and the countries of Central and Eastern Europe (CE E) has prepared? The hypothesis is that the 16+1 multilateral mechanism has created a complex network of cooperation between China and the countries of Central and Eastern Europe, which has led to positive achievements in specific subject areas. The findings show that China has planned and implemented projects and plans in the form of a win-win game with the cooperation of various groups of the above countries (Balkans, Visegrad, Axis countries), which has resulted in the reaction of other Chinese competitors.